Toward Patient Specific Models of Pediatric IVDs: A Parametric Study of IVD Mechanical Properties - Pickering, Edmund; Pivonka, Peter; Little, J. Paige (Frontiers in Bioengineering and Biotechnology, 2021)
Patient specific finite element (FE) modeling of the pediatric spine is an important challenge which offers to revolutionize the treatment of pediatric spinal pathologies, for example adolescent idiopathic scoliosis (AIS). In particular, modeling of the intervertebral disc (IVD) is a unique challenge due to its structural and mechanical complexity. This is compounded by limited ability to non-invasively interrogate key mechanical parameters of a patient's IVD. In this work, we seek to better understand the link between mechanical properties and mechanical behavior of patient specific FE models of the pediatric lumbar spine. A parametric study of IVD parameter was conducted, coupled with insights from current knowledge of the pediatric IVD. In particular, the combined effects of parameters was investigated. Recommendations are made toward areas of importance in patient specific FE modeling of the pediatric IVD. In particular, collagen fiber bundles of the IVD are found to dominate IVD mechanical behavior and are thus recommended as an area of primary focus for patient specific FE models. In addition, areas requiring further experimental research are identified. This work provides a valuable building block toward the development of patient specific models of the pediatric spine.